PENGARUH METODE MEMILAH DAN MEMILIH KARTU (CARD-SPORT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI SMAN 2 KOTO BARU KABUPATEN DHARMASRAYA - CAHYANI, FITRI - (Pendidikan Sejarah, 2014)
The reseaerch is done by low ability of the students fact understanding . This case is caused some factors, one of them is history lesson that still communicate information and make the students able to remember the lesson. One of effort is to develov understanding of fact interpretation toward choosing card-sort. The purpuse of the research is to know the effect of Choosing Card-sort Method toward the students score in history lesson at class XI SMAN 2 Koto Baru Kabupaten Dharmasraya. The adventages of this research is to support the histry teacher which innovate by using learning method in order to improve the students history score.The kinds of research are experiment research.The population of research is all of the students class XI SMAN 2 Koto Baru Dharmasraya. To do this research is needed two samples, experiment class is XI IPS 1 and control class is XI IPS 3. Based the result of research is done at XI IPS SMAN 2 koto baru and the studentsÂ  score are seen average in experiment class 7.4 . Meanwhile, average in control class is only 5.